Bioactive components of Chinese herbal medicine enhance endogenous neurogenesis in animal models of ischemic stroke: A systematic analysis. Issue 40 (October 2016) - Li, Ji-Huang; Chen, Zi-Xian; Zhang, Xiao-Guang; Li, Yan; Yang, Wen-Ting; Zheng, Xia-Wei; Chen, Shuang; Lu, Lin; Gu, Yong; Zheng, Guo-Qing
Abstract: Background: Chinese herbal medicine (CHM) has been used to treat stroke for thousands of years. The objective of the study is to assess the current evidence for bioactive components of CHM as neurogenesis agent in animal models of ischemic stroke. Methods: We searched PubMed, China National Knowledge Infrastructure, WanFang Database, and VIP Database for Chinese Technical Periodicals published from the inception up to November 2015. The primary measured outcome was one of neurogenesis biomarker, including Bromodeoxyuridine (BrdU), Nestin, doublecortin (DCX), polysialylated form of the neural cell adhesion molecule (PSA-NCAM), neuronal nuclear antigen (NeuN), and glial fibrillary acidic protein (GFAP). Results: Thirty eligible studies were identified. The score of quality assessment ranged from 2 of 10 to 7 of 10. Compared with controls, 10 studies conducting neurobehavioral evaluation showed significant effects on bioactive components of CHM for improving neurological deficits score after ischemic insults ( P < 0.01 or P < 0.05); 6 studies in Morris water-maze test showed bioactive components of CHM significantly decreased escape latency and increased residence time ( P < 0.05); 5 studies demonstrated that bioactive components of CHM significantly reduced infarct volume after ischemic stroke ( P < 0.05); 25 of 26 studies showed that bioactive components of CHM significantly increased the expression of BrdU and/or Nestin markers in rats/mice brain after ischemic injury ( P < 0.05, or P < 0.01); 4 of 5 studies for promoting the expression of PSA-NCAM or DCX biomarker ( P < 0.05); 5 studies for improving the expression of NeuN biomarker ( P < 0.05); 6 of 7 studies for promoting the expression of GFAP biomarker in brain after ischemic stroke ( P < 0.05). Conclusion: The findings suggest that bioactive components of CHM may improve neurological function, reduce infarct volume, and promote endogenous neurogenesis, including proliferation, migration, and differentiation of neural stem cells after ischemic stroke. However, evidences are supported but limited because only a few studies were available for each descriptive analysis. Further rigor study is still needed.